Qualitative evaluation: Effectiveness of utilizing digital and social media in education - ALHUMAID, K.F. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to verify the usefulness of digital media and social networks in education and recognize the possibilities of employing networks in the construction of knowledge. It is adopted a survey methodology through questioning the attitudes of teachers and students in the United Arab Emirates towards the use of social media in education. It is concluded that the technological approach, within the teaching-learning process, helps teachers and students to better tune in and communicate in ways, which have become the current life of all groups through a more flexible and sensitive teaching process. RESUMEN El estudio tiene como objetivo verificar la utilidad de los medios digitales y las redes sociales en la educación y reconocer las posibilidades de emplear redes. Se adopta la metodología de la encuesta sobre las actitudes de los docentes y estudiantes en los Emiratos Árabes Unidos hacia el uso de las redes sociales en la educación. Se concluye que el enfoque tecnológico, dentro del proceso de enseñanza-aprendizaje, ayuda a los maestros y estudiantes a sintonizarse y comunicarse mejor en formas que se han convertido en la vida actual de todos los grupos a través de un proceso de enseñanza más flexible y sensible.